1999
DOI: 10.1021/ol990791d
|View full text |Cite
|
Sign up to set email alerts
|

A Facile Method for the Solution and Solid-Phase Synthesis of Substituted [3.3.1] Bicycles

Abstract: [reaction: see text] Interest in bicyclic natural products from the Guttiferae classification has led to the development of an improved method for the selenium-mediated cyclization of alkenyl-substituted beta-dicarbonyls (I) to form a variety of bicyclo[3.3.1]nonan-9-ones (II) both in solution and on solid support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
35
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 91 publications
(36 citation statements)
references
References 17 publications
0
35
0
1
Order By: Relevance
“…In addition, it should be noted that the polystyrene-supported selenium bromide (1) is easily regenerated form the recovered methyl selenide resin (4) (Scheme 2) and can be reused for the conversion of o-allylphenol to 2-iodomentyl-2,3-dihydrobenzofurans (3). After the fourth regeneration and use, the yield and purity of 3a ( On the other hand, the other two common cleavage strategies of selenium linkers have been reported: selenoxide syn-elimination and agilent hydride transfer [19]. Although a -H exists in the above molecules, selenoxide syn-elimination did not occur when we treated resin 2 with 30 % hydrogen peroxide even when we raised the temperature to 50 °C in THF.…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…In addition, it should be noted that the polystyrene-supported selenium bromide (1) is easily regenerated form the recovered methyl selenide resin (4) (Scheme 2) and can be reused for the conversion of o-allylphenol to 2-iodomentyl-2,3-dihydrobenzofurans (3). After the fourth regeneration and use, the yield and purity of 3a ( On the other hand, the other two common cleavage strategies of selenium linkers have been reported: selenoxide syn-elimination and agilent hydride transfer [19]. Although a -H exists in the above molecules, selenoxide syn-elimination did not occur when we treated resin 2 with 30 % hydrogen peroxide even when we raised the temperature to 50 °C in THF.…”
Section: Resultsmentioning
confidence: 86%
“…Tri-n-butyltin hydride could be used here as a good radical hydride transfer reagent. For example, 2,3-dihydro-2-methylbenzofuran (4a) [20] was prepared as the described method [19] by cleavage with n-Bu 3 SnH/AIBN (Scheme 3) in 90 % overall yields, based on the selenenyl bromide resin 1. However, we did not apply this reductive cleavage to the other 2,3-dihydro-2-methylbenzofurans because n-Bu 3 SnH is a toxic reagent.…”
Section: Resultsmentioning
confidence: 99%
“…[10][11][12] Toward this end, several natural product-like templates have been tethered to a solidsupport utilizing an intramolecular, selenium-mediated cycloaddition procedure. Encouraged by their success in developing chemistry and technology to produce natural productlike libraries of oxygen-containing heterocycles and carbocyclic frameworks [13][14][15][16] and due to the potential utility of such libraries in chemical biology investigations, 17,18) they sought to expand the scope of this selenium-based solid-phase chemistry to include nitrogen-containing heterocycles. Recently, they reported that o-allyl-and o-prenyl-anilines were cycloadded to afford a series of solid-supported indole and indoline scaffolds (2) using a polymer-bound selenenyl bromide resin (Scheme 1).…”
Section: Selenium-based Solid-phase Chemistry To Include Nitrogen-conmentioning
confidence: 99%
“…24 This synthesis is expected to facilitate the total synthesis of garsubellin A and other natural products.…”
Section: Scheme 14mentioning
confidence: 99%